2019
DOI: 10.1167/tvst.8.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Endothelial Cells Over the Past Decade: Are We Missing the Mark(er)?

Abstract: Corneal endothelial dysfunction is one of the leading causes of corneal edema and visual impairment, requiring corneal endothelial transplantation. The treatments are limited, however, by both logistics and a global donor shortage. As a result, corneal researchers are striving to develop tissue-engineered constructs as an alternative. Recently, the clinical results of the first patients treated using a novel corneal endothelial cell therapy were reported, and it is likely many more will follow shortly. As we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 40 publications
1
47
0
1
Order By: Relevance
“…However, this high expression of PTGDS is consistent with a report indicating that PTGDS is expressed in both the stroma and the endothelium 38 . By contrast, expression of genes often used as endothelial markers 36 was generally high. The expression of Tight Junction Protein 1 (TJP1, also known as ZO-1) was relatively low when compared with other endothelial markers, but this lower expression level was consistent with a previous description of lower expression of TJP1 mRNA compared to TJP1 protein 26 .…”
Section: Technical Validationmentioning
confidence: 85%
See 1 more Smart Citation
“…However, this high expression of PTGDS is consistent with a report indicating that PTGDS is expressed in both the stroma and the endothelium 38 . By contrast, expression of genes often used as endothelial markers 36 was generally high. The expression of Tight Junction Protein 1 (TJP1, also known as ZO-1) was relatively low when compared with other endothelial markers, but this lower expression level was consistent with a previous description of lower expression of TJP1 mRNA compared to TJP1 protein 26 .…”
Section: Technical Validationmentioning
confidence: 85%
“…The correlation among seven samples was tested by the Spearman's rank correlation coefficient test, and the resulting correlation matrix was drawn with the 'ggcorrplot' library of R. In the heatmap analysis, the values were normalized with 'zFPKM' and heatmap analysis was performed with 'pheatmap' (both the libraries were obtained from Bioconductor). Marker genes reported to show specific expression in different corneal tissues, such as the epithelium, stroma, and endothelium, were selected as follows: PAX6 and WNT7 were referred from a representative study that performed a functional analysis of the corneal epithelium 31 ; ALDH3A1, CHST6, KERA, and PTGDS were extracted from expression markers of the corneal stroma or keratocytes commonly reported in four articles [32][33][34][35] ; and ATP1A1, TJP1, COL8A1, and SLC4A11 were selected from highly ranked investigated genes related to the corneal endothelium in a comprehensive review article 36 . The expression data of each gene used in the heatmap were evaluated for the existence of outlier samples by the Smirnov-Grubbs test with the 'outliers' library of R.…”
Section: Rna-seq Data Analysesmentioning
confidence: 99%
“…Previous studies have reported the in vitro induction of corneal endothelial-like cells derived from hESCs and hiPSCs [ 14 , 40 , 41 ], but the in vivo recovery outcome was unsatisfactory when transplantation in animal models of corneal endothelial dysfunction [ 41 ]. The most difficult is the lack of definitive specific markers to identify and enrich the differentiated CECs [ 42 , 43 ]. Moreover, the differentiated cells may experience an incomplete maturation process through the in vitro induction, although they exhibited the positive staining of several corneal endothelial cell markers.…”
Section: Discussionmentioning
confidence: 99%
“…Data of the 19,472 sequenced cells were embedded in a uniform manifold approximation and projection (UMAP) and unbiased low resolution clustering revealed five major cell clusters (Figure 1b, left). The expression of specific corneal layer marker (keratin 5 (KRT5) for epithelium 4 , keratocan (KERA) for stromal cells 5 , and transporter-like protein 11 (SLC4A11) for endothelium 6 ) identified the three main layers within the five identified clusters (Figure 1c). Differential gene expression profiling of the clusters further confirmed the identification of a corneal epithelial cell cluster comprising 5,964, a corneal stromal cell cluster comprising 12,344 cells, a corneal endothelial cell cluster comprising 842 cell, and non-corneal clusters of blood/lymphatic vessel endothelial cells comprising 36 cells, and immune cells comprising 216 cells (Figure 2).…”
Section: Five Major Cell Clusters Were Identified In the Corneal Tissuementioning
confidence: 99%